VD_FINDINFO Arrêt / 2014 / 87 vom 27. Januar 2014 - VD Tribunal cantonal (2014)
RESPONSABILITÉ DE L'EMPLOYEURAVS, COTISATION AVS/AI/APG, SOCIÉTÉ À RESPONSABILITÉ LIMITÉE | 810 al. 2 CO, 14 LAVS, 51 LAVS, 52 LAVS, 34 RAVS